Clinical and electrocardiographic predictors of left ventricular diastolic dysfunction in patients with idiopathic premature ventricular contractions - Kaypaklı, Onur; Salkın, Fatma Özge (The European Research Journal, 2025)
Objectives: Tachycardiomyopathy is a well-known phenomenon with reduction in left ventricular (LV) systolic function. In our study, we aimed to investigate the effects of idiopathic premature ventricular contractions (PVCs) on LV diastolic function in patients with idiopathic PVCs. Methods: We included 63 patients who are candidates to undergo radiofrequency ablation due to idiopathic PVCs (27 male, 36 female; mean age 47.9 ±16.6 years). Patients were classified into two groups according to the presence of LV diastolic dysfunction. The percentage of PVC burden was calculated by dividing the daily PVC burden by the total heart beat per day. Coupling interval ratio was calculated with the formula of Coupling interval ratio = (Coupling interval/sinus cycle length)x100. Results: Age, presence of q wave in D2-D3, daily PVC burden, percentage of PVC burden, left atrial volume index, intervenricular septum thickness, and mitral E/e’ ratio were significantly higher; male gender, peak E-wave velocity, lateral and septal annular e’ velocity were significantly lower in patients with LV diastolic dysfunction. Daily PVC burden and percentage of PVC burden were positively correlated with mitral E/e’ ratio and negatively correlated with lateral annular e’ velocity. The coupling interval ratio was positively correlated with mitral E/e’ ratio. Age, daily PVC burden, and percentage of PVC burden were independent predictors of increased mitral E/e’ ratio. The cutoff value of the percentage of PVC burden was 15.59% for prediction of LV diastolic dysfunction (sensitivity: 88.9%, specificity: 66.7%). Conclusions: Daily PVC burden, percentage of PVC burden, and coupling interval ratio are correlated with echocardiographic parameters of LV diastolic function.